Preparing for postpartum: health care provider discussions and predictors of patient satisfaction. Issue 4 (21st April 2021) - Schlaff, Rebecca A.; Baruth, Meghan; LaFramboise, Faith C.
ABSTRACT: Women's health care providers are trusted sources of patient education during pregnancy and postpartum; however, little is known about discussion prevalence or patient satisfaction. The purposes of this study were to describe patient-provider discussion prevalence and identify demographic and pregnancy-related factors associated with discussion occurrence and satisfaction. An electronic survey was completed by 319 postpartum women who received prenatal care for a singleton pregnancy within the last 12 months in the United States. Participants reported demographic and pregnancy-related information, and occurrence and satisfaction with information shared during prenatal and postpartum health care. Descriptive statistics and odds ratios were calculated. During pregnancy and postpartum, college graduates were more likely to report any discussion (pregnancy: OR = 1.70, 95% C.I. 1.01, 2.86; postpartum: OR = 1.94, 95% C.I. 1.16, 3.25). Participants with gestational diabetes were less likely to report any discussion during pregnancy (OR = 0.43, 95% C.I. 0.20, 0.92). Obese participants were less likely to report any postpartum discussion compared to underweight/normal weight participants (OR = 0.51, 95% C.I. 0.29, 0.89). Within postpartum health care, college graduates ( p = .01) and those with a cesarean section ( p = .01) reported lower satisfaction; multiparous women reported higher satisfaction ( p = .03). Findings highlight potential inequities in clinical practice and risk factors for postpartum anticipatory care satisfaction.